UPAYA MEWUJUDKAN GENERASI MUSLIM KAFFAH MELALUI SISTEM BOARDING SCHOOL DI LEMBAGA PENDIDIKAN ISLAM - Vivi Futika Sari; Ali Rif’an (STAI Ma'had Aly Al-Hikam Malang, 2021)
This study focuses to determine the implementation process, the role of the supporting system, and the results of the implementation of the Boarding School system as an effort to realize the generation of Muslims kaffah at MTs Ma'arif NU 2 Sutojayan - Blitar. This research is a case study that produces descriptive data. Data collection techniques include methods of observation, interviews, documentation, data analysis, and checking the validity of the data. The results are 1). the need to combine formal education with Islamic boarding schools/madrasah diniyah, 2). There are four important aspects of the role of the supporting system, namely policies, funding, human resources, and a conducive pesantren environment, 3). The challenges in its implementation are in the implementation process, the quality of educators, inputs that are not following standards, and the lack of parental support.